2008
DOI: 10.1103/physrevlett.101.115503
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Structure of Molecular Crystals from First Principles

Abstract: A recently developed method, symmetry-adapted perturbation theory based on the density-functional description of monomers [SAPT(DFT)], is shown to be sufficiently accurate and numerically efficient to facilitate predictions of the structure of molecular crystals from first principles. In one application, a SAPT(DFT) potential was used to generate and order polymorphs of the cyclotrimethylene trinitramine crystal, resulting in the lowest-energy structure in excellent agreement with the experimental crystal. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
161
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 35 publications
5
161
2
Order By: Relevance
“…4 Further estimates of three-body lattice energy contributions using symmetry-adapted perturbation theory based on densityfunctional descriptions of the monomers [SAPT(DFT)] [5][6][7][8][9][10][11][12] for crystalline benzene indicated that three-body effects contribute around 1.6 kcal mol −1 (or about 14% of the total lattice energy). 13 More recent studies 14,15 suggest that the majority of the three-body effects in crystalline benzene are due to three-body dispersion interactions, estimated to contribute 1.1 or 1.7 kcal mol −1 using the Axilrod-Teller-Muto expression (below).…”
Section: Introductionmentioning
confidence: 99%
“…4 Further estimates of three-body lattice energy contributions using symmetry-adapted perturbation theory based on densityfunctional descriptions of the monomers [SAPT(DFT)] [5][6][7][8][9][10][11][12] for crystalline benzene indicated that three-body effects contribute around 1.6 kcal mol −1 (or about 14% of the total lattice energy). 13 More recent studies 14,15 suggest that the majority of the three-body effects in crystalline benzene are due to three-body dispersion interactions, estimated to contribute 1.1 or 1.7 kcal mol −1 using the Axilrod-Teller-Muto expression (below).…”
Section: Introductionmentioning
confidence: 99%
“…We note that the intermolecular angles found in the oligoacene crystal structures (approximately 50° to 80° depending on the oligoacene) lie near the least stable intermolecular interaction energies. This points to a limitation in the current analysis, suggesting that important terms are not fully accounted for in a two-body SAPT0 approach; [129][130][131][132] thus, models aiming to predict crystal packing need to go beyond such approaches. 133 The analysis of the non-covalent interaction energies of oligoacene dimers reveals the complexity of molecular crystal engineering, with the small energy differences among rather different configurations providing a clear picture of why polymorphism is such a common phenomenon in these systems.…”
Section: The Oligoacene Seriesmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32] The polymorphism is governed by very subtle interactions, such as weak noncovalent bonds. In order to address the problem satisfactorily, theoretical methods must possess sufficient accuracy to reproduce such interactions.…”
Section: Introductionmentioning
confidence: 99%